PENGARUH SARANA BELAJAR TERHADAP MOTIVASI SISWA KELAS IV - Mulyono (JUPI (Jurnal Pendidikan Indonesia), 2023)
This study aims to determine the influence of learning facilities on the learning motivation of Madrasah Ibtidaiyyah students. This type of research is quantitative. The subjects of this study were 60 grade IV students of SD Nafi’iyyah Al-Islamiyah. The method used in this study is a descriptive method in the form of relationship studies. The results showed that there is an influence between the independent variable (X) and the dependent variable (Y) shown in Y = 14.290 + 0.721X which means the constant value is 14.290 that is, if the learning facility (X) is 0 (zero), then the learning motivation Y) is worth 14.290. The value of the correlation coefficient of the learning facility variable (X) is 0.721. This means that the increase in learning facilities by 1, then learning motivation will increase by 0.721 and the t test hypothesis test t count> t table, because the value of t count> t table is 12.044> 1.981, then Ha is accepted and Ho is rejected so that it can be concluded that there is an influence of learning facilities with student motivation.